Relevance Concept of Power Sharing According Al-Mawardi to Development of Islamic Politics in Indonesia - Bayu Karunia Putra; Azizatul Farhaini; Dinatul Aini; Siti Nurjannah; Noviana Noviana; Yulia Sasmita; Meri Zahroti; Nurul Wahidah (International Journal of Education, Information Technology, and Others, 2023)
This article aims to analyze the relevance of the concept of power sharing according to Al-Mawardi to the development of Islamic politics in Indonesia. Topic is important and interesting, because Al-Mawardi's concept of power sharing has its own relevance to the development of Islamic politics in Indonesia today. The research method used is the literature review method, where sources and data are obtained through the Publish or Perish, SINTA, and Goggle Scholar databases. In this method, researcher uses a descriptive qualitative approach, where this method utilizes qualitative data and is described descriptively. The data collection technique uses a literature review technique carried out by researchers to collect valid, complete, and relevant information related to the topic of the problem that is the object of research. The data analysis technique used a literature review analysis technique, where this research was carried out by reading library sources to obtain the necessary data. The author finds, concept of Al-Mawardi's power sharing on the development of Islamic politics in Indonesia, it can minimize problems related to the democratic system such as lack of participation from civil society, poor regeneration of political parties, and loss of opposition.